The preclinical testing of the pharmacological remedy in the Dr. melanogaster test systems (Experimental biology, 2015)
This article presents dates by studying mutagenicity of the pharmacological remedy – grossgemin in test systems Drosophila meksnjgaster: Muller-5 and X-linked chromosomes. Results of the using these methods are identical. The grossgemin mutagenic activity in concentrations of 5% in oral administration are not detected.
Keywords: drosophila; lethal mutation; solderad X-chromosomes; Meller-5; gemizigota